Pengembangan Interactive Map Website Untuk Informasi Lokasi Magang Mahasiswa Menggunakan PHP Native dan Leaflet.Js - Primayani, Sang Ayu Putu; Sanjaya, I Gede Wahyu (Journal Informatics Nivedita, 2026)
The implementation of student internship programs requires information media that can present internship location data in a structured, effective, and easily accessible manner to various parties involved. However, the management and delivery of internship location information are still often carried out conventionally, making it difficult for students to obtain internship location references and making it difficult for Study Programs to monitor the distribution of student internship locations. This study aims to develop a WebGIS-based student internship location mapping website using native PHP, MySQL, and Leaflet.js. The developed system is able to display the distribution of internship locations in the form of an interactive digital map with location marker features, filters based on categories, faculties, and majors, user location detection using Geolocation API, detailed location information, image documentation, and direction integration using Google Maps. In addition, the system provides administrator features for location data management, dashboard overview, application statistics, and category, faculty, and major data management. System development was carried out using the Waterfall method and system testing using Black Box Testing based on Functional Suitability characteristics. The test results showed that 19 test scenarios obtained valid status with a functional success rate of 100%. The test results indicate that all system features and functions have met system requirements. Thus, the website can be used as a WebGIS-based internship location information media that supports students in obtaining internship location information and helps lecturers and Study Programs in monitoring the distribution of student internship locations more effectively.